Analisis Masalah Guru Profesional Berdasarkan Kompetensi Pedagogik terhadap Kinerja Guru Pasca Diklat Pendidikan Profesi Guru di Sekolah Dasar : Literatur Review - Fuad Hasim; Tri Joko Raharjo; Harianingsih Harianingsih (Action Research Journal Indonesia (ARJI), 2025)
The background of this research focuses on the importance of the quality of education which is influenced by the ability of teachers to design and implement effective learning. This study aims to analyze the pedagogic competence of teachers and the challenges faced in their application after participating in the Teacher Professional Education (PPG) program in elementary schools. The method used is a literature review by reviewing various scientific journals from 2016 to 2024 related to pedagogic competence and teacher performance. The database information used for this article is Google Scholar. Data were obtained using the keywords "pedagogic competence," "teacher performance," and "PPG." The inclusion criteria used include journals published between 2016 and 2024, so only relevant and current articles are considered. The main focus is on how teachers' pedagogic competencies affect their performance after participating in the PPG program. The findings suggest that although PPG aims to improve teachers' skills, many struggle to apply the theories learned in daily practice. Obstacles such as lack of facilities, limited time, and school support are the main factors that hinder it. The implications of this study emphasize the need for policies that support teachers' professional development in an ongoing manner, including the provision of time for reflection and evaluation. The authors recommend that further research be conducted to explore other variables that can affect the implementation of pedagogic competencies, as well as to improve the quality of education in Indonesia as a whole.  Insert   Translations of the preposition